Harnessing the Digital Revolution for Agricultural Succession: A Multi-Site Mixed-Method Study of the 'Petani Muda Keren' (PMK) Community Network and Youth Engagement in Indonesian Food - Andi Fatihah Syahrir; Neva Dian Permana; Muhammad Faiz; Selma Fajic (Indonesian Community Empowerment Journal, 2025)
Indonesia faces a critical agricultural succession crisis, with an aging farmer population threatening the nation's long-term food security (SDG 2). Digital agrifood systems (DAS) are posited as a solution to attract youth, but adoption is uneven, and the socio-structural mechanisms facilitating this transition are poorly understood. This study investigates the role of the 'Petani Muda Keren' (PMK - Cool Young Farmers) community network, a rapidly growing grassroots movement, in bridging this gap. We employed a multi-site (West Java, Yogyakarta, West Sumatra) sequential explanatory mixed-method design. First, a quantitative survey (N=300) was conducted with PMK members (n=150) and a matched control group of non-member young farmers (n=150). We used descriptive statistics, independent t-tests, and Ordinary Least Squares (OLS) regression to analyze differences in digital adoption, productivity, and income. Second, qualitative data from 30 in-depth interviews and 6 focus group discussions with PMK leaders, members, village officials, and Ministry of Agriculture representatives were analyzed using thematic analysis to explain the quantitative findings. PMK members demonstrated significantly (p<0.001) higher adoption scores for digital technologies (such as e-commerce, farm management apps, and IoT sensors). On average, PMK members reported 34.5% higher monthly incomes and 22.8% greater farm productivity compared to non-members. The OLS regression model, controlling for education, farm size, and access to credit, confirmed that PMK membership (β=0.282, p<0.01) is a significant positive predictor of farmer income, distinct from the independent, positive effect of the digital adoption score (β=0.347, p<0.001). Qualitative analysis revealed three core mechanisms: (1) peer-to-peer mentorship de-risking technology adoption, (2) collective action for market access via network-branded e-commerce, and (3) the socio-psychological construction of a modern, 'cool' professional farmer identity. In conclusion, community-based networks like PMK function as critical social infrastructure. They are not merely passive adopters of technology but active "social bridges" that translate digital potential into tangible economic and social outcomes. They de-risk digital adoption, aggregate market power, and reframe agriculture as a high-status, viable career for the next generation. Policies aiming to achieve SDG 2 must move beyond simple technology dissemination and invest in fostering and scaling these vital social learning and innovation ecosystems.